Analisis Keaktifan Siswa Kelas 4 SDN Palebon 02 Pada Pembelajaran Matematika Melalui Media Quizizz - Widayati, Putri Arum; Siswanto, Joko (LPPM Institut Pendidikan Nusantara Global, 2024)
Improving one's perception of mathematics is vital, and as an implement, its manifestations might indeed seem diverse - an imperative embellishment of anticipation during the explanation of the study material. The established concepts generated by students would be agents to accentuating fundamental facts - of the mentioned material investigation! Students' excitement during learning is immensely critical. Implements, from these, arose influence. The knowledge process and students' engagements embody the totality as a student indicator, hence